Prevalence of type 2 diabetes using Indian diabetes risk score and its risk factors in a rural area of Tamil Nadu, India - S., Sathiya Narayanan; S., Shankar; S. K., Padmini (International Journal Of Community Medicine And Public Health, 2017)
Background: Currently the number of cases of diabetes worldwide is estimated to be around 150 million. This number is predicted to double by 2025, with the greatest number of cases being expected in China and India. In countries like India, there is also a lack of awareness about the existing interventions for preventing diabetes and the management of complications. This underscores the need for mass awareness and screening programs to identify and overcome the burden due to diabetes in India. The aim and objectives of the study was to find out the people at risk of developing diabetes using a simple risk factor scoring in a rural area in Tamil Nadu Methods: A community based cross-sectional study was carried out from June 2016 to August 2016 among 974 participants in the three rural blocks in Kancheepuram district of Tamil Nadu. A house to house visit was made and all population above 35 years of age, presenting on the day of survey were included in the study. Socio-demographic variables, risk factors were collected using a pre-tested structured questionnaire and High Risk Analysis for diabetes was done as per Indian Diabetes Risk Score (IDRS). Results: Out of 974 study subjects, 62 (6.34%) of them reported that they had diabetes. Based on the screening tool, 253 subjects were found to be in the high risk category (score >60). Proportion of subjects with high risk score in the self-reported diabetes group (58.07%) were high compared to apparently normal group (23.79%) and this difference was statistically significant (p<0.05) using Chi Square test. Conclusions: This study estimates the usefulness of simplified Indian diabetes risk score for identifying high risk diabetic subjects in the community. Use of the IDRS can make mass screening for diabetes in India more cost effective.